Pemberdayaan Ibu Cerdas: Sosialisasi Imunisasi Polio Tetes (OPV) dan Suntik (IPV) untuk Perlindungan Optimal Anak Wilayah Kerja UPTD Puskesmas Patek - Diana Lestari; Nia Hairu Novita; Yuliana Abty (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
Polio is a dangerous infectious disease that can cause permanent paralysis, but it can be effectively prevented through immunization. Optimal routine immunization coverage requires a good understanding from parents, especially mothers, as the primary decision-makers in family health. The Patek Community Health Center (Puskesmas) working area faces challenges in optimizing polio immunization coverage due to misinformation and parental concerns about side effects. This community service activity, titled "Empowering Smart Mothers," aims to improve mothers' knowledge, attitudes, and awareness regarding the importance of combining Oral Polio Vaccine (OPV) and Inactivated Polio Vaccine (IPV) to provide optimal protection for their children. This activity was carried out in the Patek Community Health Center working area and involved mothers with infants/toddlers. Methods used included interactive outreach, education using visual media (leaflets and flipcharts), and discussion/question-and-answer sessions. Evaluation of the activity's success was measured using pre-test and post-test instruments to assess participants' knowledge levels before and after the intervention. The implementation of the activity demonstrated a significant increase in mothers' understanding of the differences, schedules, and synergistic benefits of OPV and IPV. The average post-test score increased by [Insert Number]% compared to the pre-test. Furthermore, mothers' anxiety about Post-Immunization Adverse Events (AEFI) decreased drastically after receiving educational and factual explanations. Empowerment through targeted outreach has proven effective in increasing maternal health literacy regarding dual polio immunization (OPV and IPV). It is recommended that the Patek Community Health Center (Puskesmas) UPTD continue to provide ongoing education and persuasive approaches to maintain and increase national immunization coverage in the region.